Downregulation of the HCN1 Channel Alleviates Anxiety‐ and Depression‐Like Behaviors in Mice With Cerebral Ischemia–Reperfusion Injury by Suppressing the NLRP3 Inflammasome - Mei Zhou; Xiaoqin Tao; Kuan Lin; Changlong Leng; Youhua Yang; Yuran Gui; Yaojian Sun; Meiling Zhou; Binlian Sun; Yiyuan Xia; Xiji Shu; Wei Liu (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease)
Background Post‐stroke depression (PSD) is a prevalent neuropsychiatric complication of stroke. However, the mechanisms underlying PSD are still unclear. Here, we aimed to investigate the role of HCN1 (hyperpolarization‐activated cyclic nucleotide‐gated cation channel 1) in the pathogenesis of PSD and its underlying mechanisms. Methods The PSD mice model was established by middle cerebral artery occlusion in vivo. Four weeks after middle cerebral artery occlusion, anxiety‐ and depression‐like behaviors of mice were evaluated by various behavioral tests. HCN channels were downregulated by pharmacological inhibitor or neuron‐specific adeno‐associated virus. The oxygen–glucose deprivation/reoxygenation model in SY5Y cells was used to study the pathogenesis of PSD in vitro. Results Mice exhibited anxiety‐ and depression‐like behavior 4 weeks after middle cerebral artery occlusion, along with a significant increase in HCN1 protein expression in the ischemic hippocampus. Furthermore, the Ih current on neurons in the hippocampus was notably enhanced, whereas neuronal excitability was decreased in PSD mice. Treatment with HCN channel selective inhibitor ZD7288 protected SY5Y cells against oxygen–glucose deprivation/reoxygenation injury by suppressing K+ efflux. Additionally, we observed a significant increase in protein expressions of NLRP3 (nucleotide‐binding domain‐like receptor protein 3) inflammasome pathway‐related molecules in the ischemic hippocampus of PSD mice. Knockdown of HCN1 channels via virus injection into the hippocampus resulted in decreased protein expressions of NLRP3 inflammasome‐related molecules and improvement in anxiety‐ and depression‐like behaviors in PSD mice. Conclusions Downregulation of HCN1 channels has a beneficial effect on PSD by suppressing the NLRP3 inflammasome pathway, thus offering promise as a strategy for preventing and treating PSD.